Using Copper to Improve the Well-Being of the Skin - Borkow, Gadi (Current Chemical Biology, 2014)
Copper has two key properties that are being exploited in consumer and medical device products in the last decade. On the one hand, copper has potent biocidal properties. On the other hand, copper is involved in numerous physiological and metabolic processes critical for the appropriate functioning of almost all tissues in the human body. In the skin, copper is involved in the synthesis and stabilization of extracellular matrix skin proteins and angiogenesis. This manuscript reviews clinical studies that show that the use of textile consumer and medical device products, embedded with microscopic copper oxide particles, improve the well-being of the skin. These include studies showing a) cure of athlete's foot infections and improvement in skin elasticity, especially important for individuals suffering from diabetes; b) reduction of facial fine line and wrinkles; and c) enhancement of wound healing; by copper oxide embedded socks, pillowcases and wound dressings, respectively. The manuscript also reviews and discusses the mechanisms by which the presence of copper in these products improves skin well-being.
Keywords: wound healing